The Effect of the Work Environment, Work Motivation and Work Stress on Employee Work Productivity at Pt. Mitra Angkutan Sejati Pekanbaru - Suhardjo Suhardjo; Angelica Angelica; Nicholas Renaldo; Nyoto Nyoto; Onny Setyawan; Jahrizal Jahrizal (Journal of Entrepreneurial and Business Diversity, 2026)
Purpose:This study aims to determine the influence of the work environment, work motivation and work stress on the work productivity of PT. Mitra Angkutan Sejati Pekanbaru.Methodology:The population that participated in this study was all employees totaling 120 people. The sampling technique uses the census method. The analytical methods used in this study are preliminary tests, classical assumption tests, model feasibility tests, multiple linear regression analysis and so on using the help of SPSS software.Findings:The results showed that the variables of work environment, work motivation, and work stress had a significant positive effect on work productivity of PT. Mitra Angkutan Sejati Pekanbaru.Implication:Implikasi berdasarkan hasil penelitian ini, ditemukan bahwa lingkungan kerja, motivasi kerja, dan stres kerja memiliki pengaruh terhadap produktivitas karyawan di PT. Mitra Angkutan Sejati Pekanbaru.